PENERAPAN METODE FLASHCARD GAMES UNTUK MENINGKATKAN HASIL BELAJAR TENTANG MATERI KALIMAH TAYYIBAH PADA SISWA SD - Tarwita, Susanti; Yasin, Nur Ali (Jurnal Analisis Pendidikan Sosial, 2025)
The learning outcomes of third-grade students at SD Negeri Klatak Banyuwangi on the theme “Aku Senang Berkalimah Tayyibah” were low during the pre-cycle stage, with an average score of 63 and a mastery level of 36.36%. This underachievement was attributed to conventional teaching methods that lacked active student engagement. This study aims to improve students’ learning outcomes through the implementation of flashcard games, an interactive and enjoyable learning approach. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observations, and interviews and were analyzed descriptively using qualitative and quantitative methods. The results demonstrated significant improvement in each cycle. In cycle 1, the average student score increased to 78.36, with a mastery level of 66.67%. In cycle 2, the average score reached 90, with 100% mastery. The flashcard games method effectively enhanced students’ understanding of the material, motivated them to learn actively, and created an interactive learning environment. This study recommends applying similar methods in other subjects to improve the quality of education.